2020
DOI: 10.1101/2020.05.20.107219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome and epigenome diversity and plasticity of muscle stem cells following transplantation

Abstract: 20Adult skeletal muscles are maintained during homeostasis and regenerated upon injury by muscle stem 21 cells (MuSCs). A heterogeneity in self-renewal, differentiation and regeneration properties has been 22 reported for MuSCs based on their anatomical location. Although MuSCs derived from extraocular 23 muscles (EOM) have a higher regenerative capacity than those derived from limb muscles, the 24 molecular determinants that govern these differences remain undefined. Here we show that EOM and 25 limb MuSCs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 98 publications
(93 reference statements)
1
11
0
Order By: Relevance
“…Our DNA methylome analysis also revealed hypermethylation of the Hox-A loci and high expression levels of Hox-A cluster genes in adult limb muscles and their associated satellite cell-derived myoblasts. Although these loci are not uniformly hypermethylated and the DNA hypermethylation patterns do not simply correlate with the expression levels of Hox-A cluster genes, our findings are further supported by the study depicting the hypermethylation status of Hox-A loci in hindlimb-derived satellite cells in mice (24). In addition to DNA methylation, histone modifications may also be involved in regulating Hox-A gene cluster expression in satellite cells (23,34).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Our DNA methylome analysis also revealed hypermethylation of the Hox-A loci and high expression levels of Hox-A cluster genes in adult limb muscles and their associated satellite cell-derived myoblasts. Although these loci are not uniformly hypermethylated and the DNA hypermethylation patterns do not simply correlate with the expression levels of Hox-A cluster genes, our findings are further supported by the study depicting the hypermethylation status of Hox-A loci in hindlimb-derived satellite cells in mice (24). In addition to DNA methylation, histone modifications may also be involved in regulating Hox-A gene cluster expression in satellite cells (23,34).…”
Section: Discussionsupporting
confidence: 75%
“…Our ectopic transplantation study shows that MAS-derived satellite cells maintained low Hox status 2 weeks following TA niche exposure. However, Evano et al (24) reported that satellite cells isolated from the extraocular muscle, which is derived from the cranial mesoderm, express Hox-A cluster genes at very low levels, but these genes are up-regulated 3 to 4 weeks after transplantation into CTX preinjected TA muscle. This discrepancy may be explained by the different time periods after transplantation or different cell types: A longer duration of exposure to different niches may gradually influence Hox status, or extraocular muscle-derived satellite cells may adapt to different niches compared to MAS-derived satellite cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MuSCs are heterogeneous populations with different cell cycling times [24,25], Pax3 [26], Pax7 [27], Myf5 [28], Mx1 [29], or CD34 expression [30]. In addition, MuSC properties are also influenced by myofiber type [31] or the muscle region in the body [32]. MuSCs in both slow (soleus) and fast-type muscles (plantaris) can supply new myonuclei in loading muscles [33,34], suggesting that the responsiveness of MuSCs to mechanical loading is not dramatically different between slow and fast myofibers.…”
Section: Muscle Stem Cells Markersmentioning
confidence: 99%